International Taxation and Productivity Effects of M&As - Maximilian Todtenhaupt; Johannes Voget (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We investigate how changes in firm productivity after M&As are affected by differences in profit taxation between the target and the acquirer. We argue that tax differentials distort the efficient allocation of productive factors following an M&A and thus inhibit the realization of productivity improvements. Using firm-level data on inputs and outputs of production as well as on corporate M&As, we show that the absolute tax differential between the locations of two merging firms reduces the subsequent total factor productivity gain. This effect is concentrated in horizontal M&As and less pronounced when firms can use international profit shifting to attenuate effective differences in taxation.
Keywords: F23; H25; 330; M&A; productivity; international taxation